2019
DOI: 10.1038/s41598-019-52845-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the clavicle’s muscle insertion footprints – a cadaveric study

Abstract: The muscle footprint anatomy of the clavicle is described in various anatomical textbooks but research on the footprint variation is rare. Our goal was to assess the variation and to create a probabilistic atlas of the muscle footprint anatomy. 14 right and left clavicles of anatomical specimens were dissected until only muscle fibers remained. 3D models with muscle footprints were made through CT scanning, laser scanning and photogrammetry. Then, for each side, the mean clavicle was calculated and non-rigidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although this is a promising approach, there were also outliers in the measurement that had to be removed manually. Herteleer et al [ 22 ] showed the variation of muscle attachment areas in the clavicle. However, they did not analyze the knee-relevant muscle areas or the centroids of the attachment areas.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a promising approach, there were also outliers in the measurement that had to be removed manually. Herteleer et al [ 22 ] showed the variation of muscle attachment areas in the clavicle. However, they did not analyze the knee-relevant muscle areas or the centroids of the attachment areas.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies previously reported a poor geometric fit of the current fixation plates 5,6 . Additionally, these plates interfere with soft tissues 7 due to the high variability of the clavicle shape 8,9 and its muscle attachment sites (MAS) 10 . To overcome these issues, intraoperative bending of the plate is often required to achieve an appropriate fit.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Additionally, these plates interfere with soft tissues 7 due to the high variability of the clavicle shape 8,9 and its muscle attachment sites (MAS). 10 To overcome these issues, intraoperative bending of the plate is often required to achieve an appropriate fit. Nevertheless, part of the MAS sometimes still has to be detached.…”
mentioning
confidence: 99%